Recent advances in understanding the genetics of congenital heart defects - Gelb, Bruce D. (2013)
PURPOSE OF REVIEW: To review recent advances in our understanding of the genetic causes of congenital heart disease (CHD). RECENT FINDINGS: CHD behaves like a complex genetic trait in most instances. Recent advances in genomics have provided tools for uncovering genetic variants underlying complex traits that are now being applied to study CHD. Massively parallel DNA sequencing has shown that de novo mutations contribute to ~10% of severe CHD and implicated chromatin remodeling in pathogenesis. Genome scanning methods for copy number variants continue to identify lesions underlying CHD, some predisposing to it generally and others having lesion specificity. Gene-environment interactions are being explored, primarily related to the metabolism of folate and homocysteine. Finally, studies are addressing other aspects of complexity for CHD such as mutations in cis-regulatory elements and modifying genes. SUMMARY: The genetic architecture of CHD is being elaborated through the use of state-of-the-art genomic approaches. Through these scientific advances, new opportunities for preventing and ameliorating CHD and its co-morbidities are anticipated.